OPTIMISATION OF GENERATOR ROTATION IN HINGED BLADE KINETIC TURBINES USING GEAR BOX TRANSMISSION: IMPLICATIONS IN EDUCATIONAL SETTINGS - Boedi, Silvy Dollorossa (CV. TOTUS TUUS, 2025)
Microhydro power generation (MHP) is increasingly recognized as a clean, renewable energy solution, particularly in rural and off-grid regions. However, one fundamental challenge in MHP systems is the instability of turbine rotational speed and torque, which compromises energy conversion efficiency. This study aimed to design, construct, and evaluate a hinged blade vertical axis kinetic turbine integrated with a planetary gearbox transmission to overcome such limitations, especially in low-head and low-flow irrigation canal conditions. The research employed an experimental method involving design, fabrication, and field testing of the prototype, with measurements focusing on voltage, current, rotational speed, and power output under varying loads. The system demonstrated a significant performance increase, with turbine speed amplified from an average of 256.35 rpm (no-load) to 923.70 rpm (with load), and a peak electrical output of 8.80 watts—suitable for basic rural applications such as lighting and charging. These results confirmed the system’s operational reliability and synchronization between mechanical and electrical components. The research contributes practical insights into integrated microhydro systems and offers a replicable model for both rural electrification and engineering education. It is especially relevant for vocational training and renewable energy curriculum development. Future studies are encouraged to explore computational fluid dynamics modeling, IoT-based monitoring, and hybrid solar integration to further enhance system performance and scalability.